Bridging Markets and Margins: Strategic Business Innovations for Sustainable Livelihoods and Competitive Positioning in Low-Income Economies - Donald L. Montenegro (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2025)
This study explores how micro, small, and medium enterprises (MSMEs) in low-income economies can strategically innovate to enhance both their market competitiveness and their contributions to sustainable community development. Focusing on innovations in products, distribution systems, and service delivery, the research investigates how businesses can create value that balances profitability with social impact. Despite increased attention to inclusive business models, many enterprises in marginalized regions still face challenges such as limited scalability, lack of integration between commercial and social goals, and inadequate support systems. This research addresses key gaps, including the under exploration of service and distribution innovations, limited empirical data on long-term outcomes, and the absence of frameworks that align business strategy with inclusive development. Through a mixed-methods approach involving case studies, surveys, and interviews, the study will identify patterns of innovation, analyze enabling and limiting factors, and propose a Strategic Innovation Framework tailored to MSMEs operating in resource-constrained environments. The findings aim to offer practical insights for entrepreneurs and development stakeholders, while contributing to academic discourse on sustainable and inclusive entrepreneurship. Ultimately, the study aspires to empower MSMEs to become catalysts of economic resilience and social progress within their communities, fostering models that are viable, scalable, and adaptable across similar socio-economic settings.